Advances in Bioengineering 2003
DOI: 10.1115/imece2003-43174
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Postural Stability Testing During Standup Forklift (Lift Truck) Operation

Abstract: This paper investigates the threshold of dynamic postural stability during standup forklift (lift truck) operation. Through a series of controlled tests, live subject data is gathered to determine the effect of upper extremity support during acceleration perturbation of the forklift (standing platform). The level of perturbation causing loss of balance is in close agreement with earlier studies and supports the use of a door in a standup forklift to arrest loss of balance, falling and injury during routine sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous studies have examined the issue of longitudinal acceleration and deceleration and found the acceleration levels to cause loss of balance. 1,2 Another injury mechanism that can occur to the lower limb of a stand up lift truck can occur due to intrusion into the operator compartment of the truck. When forklifts are traveling in queue, in a forks leading manner, and the following forklift fails to decelerate at the same time as the lead forklift, the forks on the trailing forklift can intrude into the operator compartment of the lead forklift.…”
Section: Figurementioning
confidence: 99%
“…Previous studies have examined the issue of longitudinal acceleration and deceleration and found the acceleration levels to cause loss of balance. 1,2 Another injury mechanism that can occur to the lower limb of a stand up lift truck can occur due to intrusion into the operator compartment of the truck. When forklifts are traveling in queue, in a forks leading manner, and the following forklift fails to decelerate at the same time as the lead forklift, the forks on the trailing forklift can intrude into the operator compartment of the lead forklift.…”
Section: Figurementioning
confidence: 99%
“…As one of the most common field (factory) special motor vehicles [1] , forklift brings the flexibility, efficiency and convenience to the warehouse, wharf cargo handling, stacking, short distance transportation and other production operations on one hand [2][3][4][5] . On the other hand, because of short driving distance, workload, stating& braking frequently, not standardized management, prominent safety problem and any effective maintenance or replacement for the mechanical failure timely, it often causes such goods dumped or vehicle rollover accidents [6,7] .…”
Section: Introductionmentioning
confidence: 99%